Use of bedaquiline in the chemotherapy regimen for multiple drug resistant tuberculosis in the HIV positive patient - N. D. Pirogova; S. N. Leshok; L. V. Schipunova; N. G. Beloborodova (Туберкулез и болезни лёгких, 2019)
The article describes a clinical case of the effective treatment of multiple drug resistant respiratory tuberculosis in the HIV positive patient. The chemotherapy regimen consisted of 5 anti-tuberculosis drugs, including bedaquiline, and 3 antiretroviral (ARV) drugs. The combined use of bedaquiline and ARV therapy did not result in any adverse reactions.